Alkylation of the α-amino C–H bonds of anilines photocatalyzed by a DMEDA-Cu-benzophenone complex: reaction scope and mechanistic studies. Issue 26 (10th June 2021) - Abadie, Baptiste; Jonusauskas, Gediminas; McClenaghan, Nathan D.; Toullec, Patrick Y.; Vincent, Jean-Marc
Abstract : The Cu(ii ) complex 1 incorporating a BP chromophore is a highly active photocatalyst for the alkylation of α-amino C–H bonds of anilines. Mechanistic studies revealed the spectroscopic signatures of the key reaction intermediates. Abstract : The Cu(ii ) complex 1 incorporating a BP chromophore is a highly active and chemoselective photocatalyst for the alkylation of α-amino C–H bonds of anilines. The reaction was shown to proceed with a broad substrate scope in the absence of additives. Extensive mechanistic studies were performed, in particular using transient absorption spectroscopy, and spectroscopic signatures of key intermediates were identified in the conditions of catalysis. Finally, the ability of 1 to act as a multitask catalyst was showcased by conducting multi-component CuAAC and olefin hydroalkylation reactions in one-pot.